Pain Assessment in Children. Issue 3 (March 2015) - Chang, Julie; Versloot, Judith; Fashler, Samantha R.; McCrystal, Kalie N.; Craig, Kenneth D.
<x xml:space="preserve">Abstract</x> Objectives: Assessing pain in young children requires astute judgment by observers. Multidimensional observational scales for pediatric pain contribute by providing behavioral cues believed to characterize pain in children; yet, few measurement items have undergone rigorous psychometric evaluation. This is the case with facial expression, which has been widely recognized as the most sensitive and specific nonverbal indicator of pain. The criteria for identifying facial expressions of pain differ substantially across scales and are frequently inconsistent with empirical descriptions. Materials and Methods: The present study compared observer ratings of children's (aged 1 to 6 y, inclusive) videotaped postoperative pain reactions using the facial activity items from 6 widely used pediatric pain assessment scales and an anatomically based and empirically validated measure, the Child Facial Coding System. We hypothesized that facial expression items that did not correspond to empirical descriptions would lead to less reliable and divergent pain estimates. Intercoder reliability, criterion validity (empirical and convergent), content validity, and face validity were examined. Results: Findings supported hypotheses and indicated that variation in cues proposed for assessing facial expression led to widely ranging scores that could be insensitive to differences in children's pain intensity. Discussion: The facial items varied considerably in coder judgment reliability as well as criterion (empirical and convergent), content, and face validity. Observational scales should provide behavioral cues that correspond to empirical descriptions of the facial expression of pain.